Force production during maximal effort bend sprinting: Theory vs reality - Churchill, S. M.; Trewartha, G.; Bezodis, I. N.; Salo, A. I. T. (Scandinavian Journal of Medicine & Science in Sports, 2016)
This study investigated whether the "constant limb force" hypothesis can be applied to bend sprinting on an athletics track and to understand how force production influences performance on the bend compared with the straight. Force and three-dimensional video analyses were conducted on seven competitive athletes during maximal effort sprinting on the bend (radius 37.72 m) and straight. Left step mean peak vertical and resultant force decreased significantly by 0.37 body weight (BW) and 0.21 BW, respectively, on the bend compared with the straight. Right step force production was not compromised in the same way, and some athletes demonstrated substantial increases in these variables on the bend. More inward impulse during left (39.9 ± 6.5 Ns) than right foot contact (24.7 ± 5.8 Ns) resulted in 1.6° more turning during the left step on the bend. There was a 2.3% decrease in velocity from straight to bend for both steps. The constant limb force hypothesis is not entirely valid for maximal effort sprinting on the bend. Also, the force requirements of bend sprinting are considerably different to straight-line sprinting and are asymmetrical in nature. Overall, bend-specific strength and technique training may improve performance during this portion of 200- and 400-m races.